12 incredible facts about the Montgomery Bus Boycott - Sepahban, Lois (Turning points in US history (12 Story Library (Firm)), 2016)
Provides twelve facts about the Montgomery Bus Boycott, a civil rights protest sparked by seamstress Rosa Parks' refusal to give up her seat on a bus to a white passenger in 1955.